Taá¸¥lÄ«l Niáº“am FiÄt Al-TafÄâ€™ul Al-Lafáº“i (VICS) fi Taâ€™lÄ«m Al-Lugah Al-Arabiyyah - faisal mubarak; Ahmad Abdul Rahman (Arabic Education Program IAIN Pekalongan, 2019)
This research is focused on the interaction of teachers and students of madrasah stanwiyah in the classroom, the purpose of this study is to know the pattern of learning interaction takes place. Between teachers and students in class that occurred in Madrasah Stnawiyah. Especially in the process of learning Arabic language, which is located in MTs. Barabai. The method of reseach is field research. In terms of theoretical, the results of this study is expected to be a reference, to know how good interaction between teachers and students so as to enhance the activity of learning in the classroom.